TEMPERAMEN, INTERAKSI IBU-REMAJA, DAN KECERDASAN EMOSI REMAJA PADA KELUARGA DENGAN IBU BEKERJA DI PERDESAAN - Ramadhianti, Nadya; ., Alfiasari (Jurnal Ilmu Keluarga dan Konsumen, 2017)
This study aimed to analyze the influence of adolescent characteristics and family characteristics on mother-adolescent interactions and analyzing the influence of adolescent characteristics, family characteristics, and mother-adolescent interactions on adolescent emotional intelligence in adolescent with working mother. This research was conducted in Ciampea, Bogor Regency that chosen purposively with consideration as rural area and location of home industry. The design of this research is cross-sectional study. Samples are adolescents with working mothers, from four selected junior high schools. Total samples were 160, consist of 80 mothers and adolescents that selected purposively. In the first regression model, it was found that effortful control (dimension of adolescent temperament) has a significant positive effect on mother-adolescent interaction. Meanwhile, negative affectivity (dimension of adolescent temperament) has a significant negative effect on mother-adolescent interaction. Furthermore, in the second regression model found that mother-adolescent interaction (adolescent version) has a significant positive effect on adolescent emotional intelligence.